Robotic central pancreatectomy: a systematic review and meta-analysis. Issue 2 (February 2022) - Rompianesi, Gianluca; Montalti, Roberto; Giglio, Mariano C.; Caruso, Emanuele; Ceresa, Carlo DL.; Troisi, Roberto I.
Abstract: Background: Central pancreatectomy is usually performed to excise lesions of the neck or proximal body of the pancreas. In the last decade, thanks to the advent of novel technologies, surgeons have started to perform this procedure robotically. This review aims to appraise the results and outcomes of robotic central pancreatectomies (RCP) through a systematic review and meta-analysis. Methods: A systematic search of MEDLINE, Embase, and Web Of Science identified studies reporting outcomes of RCP. Pooled prevalence rates of postoperative complications and mortality were computed using random-effect modelling. Results: Thirteen series involving 265 patients were included. In all cases but one, RCP was performed to excise benign or low-grade tumours. Clinically relevant post-operative pancreatic fistula (POPF) occurred in 42.3% of patients. While overall complications were reported in 57.5% of patients, only 9.4% had a Clavien-Dindo score ≥ III. Re-operation was necessary in 0.7% of the patients. New-onset diabetes occurred postoperatively in 0.3% of patients and negligible mortality and open conversion rates were observed. Conclusion: RCP is safe and associated with low perioperative mortality and well preserved postoperative pancreatic function, although burdened by high overall morbidity and POPF rates.